MON-321 AgRP and Food Cravings Decrease with Treatment of Cushing’s Disease - Haseltine, Katherine N (J Endocr Soc, 2020)
Cushing’s disease (CD) is characterized by chronic exposure to excess glucocorticoids due to an ACTH-producing tumor. Obesity is a prominent feature of CD, although the mechanisms of weight gain have not been completely elucidated. In some patients, obesity persists despite appropriate medical or surgical treatment of CD and normalization of cortisol levels (1). Few studies have followed patients prospectively to understand the effect of CD remission and cortisol normalization on appetite and body weight. Previous studies have not shown a correlation between appetite or food cravings and circulating total peptide YY (PYY), ghrelin, or leptin concentrations, leading to interest in other hormones which may regulate appetite in CD (2). One of these is the neuropeptide Agouti-related protein (AgRP). AgRP is known to promote appetite and decrease energy expenditure by acting as a melanocortin antagonist at the level of the hypothalamus. Plasma AgRP may be elevated in patients with active CD and decreases with normalization of cortisol levels (3). We sought to determine if AgRP may play a role in regulating appetite or food cravings in CD. Plasma AgRP was measured before and prospectively after treatment in 19 patients with CD. Patients completed surveys on appetite and food cravings at these same time points. As expected, AgRP significantly decreased following treatment for CD, with mean AgRP before treatment 128.72 pg/mL (SD 55.41) and mean AgRP after treatment 75.23 pg/mL (SD 23.46). Using a paired t-test, the mean difference of 53.5 pg/mL was significant (p=0.0006). In addition, there were significant decreases in BMI, weight, and waist circumference with CD treatment. We found that plasma AgRP concentrations did not correlate with an 8-question visual analogue scale (VAS) used to assess hunger and satiety. However, treatment of CD significantly reduced Trait Food Craving Questionnaire scores in parallel with circulating AgRP levels using a one-way analysis of variance (p=0.004). Our data suggest that AgRP may play a role in food craving, rather than appetite, in patients with CD. Further research may clarify the relationship between AgRP and food cravings in CD patients before and after treatment. References: 1. Geer et al. Endocrinol Metab Clin North Am. 2014; 43: 75-102. Geer et al. Pituitary. 2016; 19: 117-126.Page-Wilson et al, J Clin Endocrinol Metab. 2019; 104 (3): 961-969.